2014
DOI: 10.5507/ag.2014.007
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of specific on-ice repeated-sprint ability test for ice-hockey players

Abstract: Background: Repeated sprint ability tests are today widely used to evaluate the performance capability in team sports. Objective: The aim of this study was to determine the reliability of a specific ice hockey test, which indicates the agility and repeated-sprint ability of the players. Methods: Twenty four highly trained junior ice hockey players (age = 17.68 ± 1.52 years; BMI = 23.8 ± 1.92 kg · m -2 ) participated in the study. Each participant was assessed for specific on-ice repeated-sprint ability test 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Using this criterion the only variable with significantly unsatisfactory absolute reliability was S dec (38.85%). Gabbett (2010), Spencer et al (2005), Glaister et al (2009) and Hůlka, Bělka, Cuberek, and Schneider (2014) reported a similar problem and concluded that S dec cannot be recommended as a fatigue indicator in fatigue protocols due to its high variability. We think that the S dec index is too sensitive to extreme values of attempts.…”
Section: Bsfp 28 Measurement Reliabilitymentioning
confidence: 92%
“…Using this criterion the only variable with significantly unsatisfactory absolute reliability was S dec (38.85%). Gabbett (2010), Spencer et al (2005), Glaister et al (2009) and Hůlka, Bělka, Cuberek, and Schneider (2014) reported a similar problem and concluded that S dec cannot be recommended as a fatigue indicator in fatigue protocols due to its high variability. We think that the S dec index is too sensitive to extreme values of attempts.…”
Section: Bsfp 28 Measurement Reliabilitymentioning
confidence: 92%
“…This test was originally designed by H ůlka et al [13], based on the work rate profiles e.g., movement pattern and duration of each sprint of the players found during match play. In this test, the subjects were required to perform 6 sets of 3 × 80-m sprint trials.…”
Section: Repeated Sprint Skating Ability Testmentioning
confidence: 99%
“…Každý nově konstruovaný kondiční test, jehož úkolem je buď poukázat na kondiční způsobilost podávat optimální výkon v utkání, anebo simulovat únavu, která je co nejvíce podobná té po utkání. Je proto nutné co nejlépe ověřit vlastnosti těchto protokolů (Hůlka, Bělka, Cuberek, & Schneider, 2014). Pro jejich využitelnost v praxi se po zkonstruování protokolu ověřuje reliabilita a validita protokolu.…”
Section: úVodunclassified